THE EFFECTS OF AUDIT QUALITY ON FIRM VALUE OF INDONESIAN FINANCIAL SERVICE SECTOR (FSS) - Alexandra A. Yolandita; Nur Cahyonowati (Diponegoro Journal of Accounting, 2022)
This paper aims to examine the effect of audit quality, based on the signalling theory, on firm value in the Indonesian financial service sector from 2016 to 2020. This study uses audit firm size (Big Four vs. Non-Big Four) to measure audit quality and Tobin’s Q to proxy firm value. Using 60 samples of financial service firms listed on the Indonesia Stock Exchange for 5 years, this study finds that audit quality has a significantly negative effect on firm value in the Indonesian financial service sector. Higher quality audits in this sector cannot be determined by merely using the Big Four or non-Big Four auditors’ audit service. This study suggests that companies and regulators view Big Four and Non-Big Four auditors equally based on their performance.